Progress towards a high acquisition rate attosecond pump-probe beamline - Furch, Federico J.; Witting, Tobias; Schell, Felix; Hoff, Dominik; Lu, Chih Hsuan; Ssusnjar, Peter; Cavalcante, Fabio; Menoni, Carmen; Schulz, Claus P.; Paulus, Gerhard G.; Kung, A. H.; Vrakking, Marc J.J. (2018 Conference on Lasers and Electro-Optics, CLEO 2018 - Proceedings, 2018)
The development of an attosecond pump-probe beamline based on a 100 kHz laser system is presented. Results on high harmonic generation, pulse shortening towards the single-cycle limit and single-shot carrier-envelope phase characterization are discussed.
CRIS-Team Scopus Importer:2023-04-20